Kannan Type Mapping in Tvs-Valued Cone Metric Spaces and Their Application to Urysohn Integral Equations - Azam, Akbar; Beg, Ismat (Sarajevo Journal of Mathematics, 2024)
We obtain sufficient conditions for the existence of a common fixed point of three mappings satisfying Kannan type conditions in TVS valued cone metric spaces. We also give an application by finding the solution for a system of two Urysohn integral equations. Our results generalize several well-known recent results in the literature. 2010 Mathematics Subject Classification. 47H10, 47H09, 45N05, 46N20 54H25.